2003
DOI: 10.1002/bjs.4071
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic disease does not contraindicate hepatectomy for colorectal liver metastases

Abstract: Extrahepatic disease in patients with colorectal cancer who also have liver metastases should no longer be considered an absolute contraindication to hepatectomy. However, the presence of more than five liver metastases and the incidental intraoperative discovery of extrahepatic disease remain contraindications to hepatic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
126
1
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(138 citation statements)
references
References 31 publications
4
126
1
7
Order By: Relevance
“…Historically, concerns regarding the safety of such an extensive operation have been raised, but most series reported in the last decade revealed that the short-term results achieved in these patients were similar to those observed in patients undergoing surgery for liver-limited metastases (10,26,27). A similar trend was also observed in the present series, with no significant differences in morbidity and mortality rates between CHMs group and CHEHMs group, except for the patients undergoing major hepatectomies in the early period of this study.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Historically, concerns regarding the safety of such an extensive operation have been raised, but most series reported in the last decade revealed that the short-term results achieved in these patients were similar to those observed in patients undergoing surgery for liver-limited metastases (10,26,27). A similar trend was also observed in the present series, with no significant differences in morbidity and mortality rates between CHMs group and CHEHMs group, except for the patients undergoing major hepatectomies in the early period of this study.…”
Section: Discussionmentioning
confidence: 92%
“…In 2003, Elias et al reported (in a study of 111 patients with CHEHMs) a 5-year overall survival rate of 20% (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A careful and individual evaluation of (67,74), and also series with simultaneous resection of hepatic and extrahepatic metastases have demonstrated 5-year survival rates approaching 30% (45,75). The intrahepatic tumour number as an exclusion criterion for liver surgery is still a matter of debate.…”
Section: Resection Of Recurrencementioning
confidence: 99%